Influência do peso adicional nos chutes de lactentes de um a quatro meses de vida - Landgraf, Jocelene de Fátima (2011)
This study aimed to describe the method used for the kinematic analysis of kicking movements in infants and to determine the effect of additional weighting in the pattern of the kicking movements of infants in the first four months of life. For this, two studies are presented. The first study describes the method used for the kinematic analysis of kicking movements in infants. In the study, four infants were longitudinally videotaped at ages from one to six months and analysis was performed on the Dvideow system. It was verified that the use four video cameras was required. Moreover, six plumb lines were used to calibrate the system and ensure an accuracy of 2 mm. It was concluded, based in the first estudy that the use of the Dvideow system to perform kinematic analysis of the kicking movement in infants proved to be appropriate and feasible. The second study aimed to verify the influence of weights of 1/10 e 1/3 the mass of lower limb in the pattern of the kicking movements of infants in the first four months of life. Fourteen healthy infants participated in the study, longitudinally videotaped. Kicking frequency, foot/panel contact frequency, intralimb coordination pattern, movement time, average speed and straightness index were analyzed. Comparing the ages, we found differences in the kicking frequency, foot/panel contact frequency, movement time, and average speed. Comparing the weighting conditions, we found changes in the kicking frequency and foot/panel contact frequency; the kinematic variables remained unchanged. Therefore, we suggest that during the first four months of life, infants change the kicking frequency according to their ages, the intra-session training and additional weighting. These features are probably the result of intrinsic factors such as increased mass and muscle strength, behavior status of infants, maturation of the Central Nervous System and extrinsic factors such as the weight and the interest in the environment and in performing the proposed task.